2003
DOI: 10.1101/gad.256603
|View full text |Cite
|
Sign up to set email alerts
|

MAX4andRMS1are orthologous dioxygenase-like genes that regulate shoot branching inArabidopsisand pea

Abstract: Shoot branching is inhibited by auxin transported down the stem from the shoot apex. Auxin does not accumulate in inhibited buds and so must act indirectly. We show that mutations in the MAX4 gene of Arabidopsis result in increased and auxin-resistant bud growth. Increased branching in max4 shoots is restored to wild type by grafting to wild-type rootstocks, suggesting that MAX4 is required to produce a mobile branch-inhibiting signal, acting downstream of auxin. A similar role has been proposed for the pea ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
601
0
18

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 533 publications
(649 citation statements)
references
References 34 publications
30
601
0
18
Order By: Relevance
“…Previous studies have shown that auxin positively regulates SMS synthesis gene expression (Sorefan et al, 2003;Bainbridge et al, 2005;Foo et al, 2005;Johnson et al, 2006;Arite et al, 2007), also suggesting that strigolactones could function downstream of auxin to inhibit bud outgrowth. Auxin regulation of the expression of the SMS synthesis gene CCD8 was demonstrated to be AXR1 dependent in Arabidopsis (Bainbridge et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Previous studies have shown that auxin positively regulates SMS synthesis gene expression (Sorefan et al, 2003;Bainbridge et al, 2005;Foo et al, 2005;Johnson et al, 2006;Arite et al, 2007), also suggesting that strigolactones could function downstream of auxin to inhibit bud outgrowth. Auxin regulation of the expression of the SMS synthesis gene CCD8 was demonstrated to be AXR1 dependent in Arabidopsis (Bainbridge et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…Auxin has been shown to promote the expression of SMS synthesis genes (Sorefan et al, 2003;Bainbridge et al, 2005;Foo et al, 2005;Johnson et al, 2006;Arite et al, 2007). As a result, branching mutants defective in auxin response may have reduced strigolactone biosynthesis, which may be the cause of their increased branching phenotype.…”
Section: Strigolactone Reduces Branching In Auxin Response Increased mentioning
confidence: 99%
See 3 more Smart Citations